Affective Equality - Lynch, K. author. aut Link
XII, 289 p.
Keywords: This groundbreaking book provides a new perspective on equality by highlighting and exploring affective equality, the aspect of equality concerned with relationships of love, care and solidarity. Drawing on studies of intimate caring, or 'love labouring', it reveals the depth, complexity and multidimensionality of affective inequality.